Nivel de importaciones y el crecimiento económico en el centro ferial Sachachorro de Iquitos, periodo 2024 - Casanova Daza, Jose Luis (2025)
The objective of the research is to determine the relationship between the level of imports and economic growth at the Sachachorro Fair Center in Iquitos during the period 2024, with a quantitative research approach of a non experimental design of a cross-sectional design type, with a correlational study scope; included as a study population 185 merchants who operate in the Sachachorro Fair Center, Iquitos, I concluded that the correlations obtained between the variables related to imports (level of imports, types of imported goods, diversity of imported products, frequency of imports) and economic growth show a significant positive relationship. This indicates that imports play a relevant role in driving economic growth, improving access to goods and services that can enhance the competitiveness and productivity of the local economy, in addition to the significant correlations between the various dimensions of imports and economic growth suggest an interdependence between these factors. Not only imports, but also their diversity, frequency and types, influence the creation of a more competitive and productive environment that favors economic growth.